Global transcriptome analysis of two wild relatives of peanut under drought and fungi infection - Guimarães, Patricia Messenberg (2012)
Background: Cultivated peanut (Arachis hypogaea) is one of the most widely grown grain legumes in the world, being valued for its high protein and unsaturated oil contents. Worldwide, the major constraints to peanut production are drought and fungal diseases. Wild Arachis species, which are exclusively South American in origin, have high genetic diversity and have been selected during evolution in a range of environments and biotic stresses, constituting a rich source of allele diversity. Arachis stenosperma harbors resistances to a number of pests, including fungal diseases, whilst A. duranensis has shown improved tolerance to water limited stress. In this study, these species were used for the creation of an extensive databank of wild Arachis transcripts under stress which will constitute a rich source for gene discovery and molecular markers development. Results: Transcriptome analysis of cDNA collections from A. stenosperma challenged with Cercosporidium personatum (Berk. and M.A. Curtis) Deighton, and A. duranensis submitted to gradual water limited stress was conducted using 454 GS FLX Titanium generating a total of 7.4 x 105 raw sequence reads covering 211 Mbp of both genomes. High quality reads were assembled to 7,723 contigs for A. stenosperma and 12,792 for A. duranensis and functional annotation indicated that 95% of the contigs in both species could be appointed to GO annotation categories. A number of transcription factors families and defense related genes were identified in both species. Additionally, the expression of five A. stenosperma Resistance Gene Analogs (RGAs) and four retrotransposon (FIDEL-related) sequences were analyzed by qRT-PCR. This data set was used to design a total of 2,325 EST-SSRs, of which a subset of 584 amplified in both species and 214 were shown to be polymorphic using ePCR. Conclusions: This study comprises one of the largest unigene dataset for wild Arachis species and will help to elucidate genes involved in responses to biological processes such as fungal diseases and water limited stress. Moreover, it will also facilitate basic and applied research on the genetics of peanut through the development of new molecular markers and the study of adaptive variation across the genus.